2007
DOI: 10.1111/j.1460-9568.2007.05614.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of mGlu1 and mGlu5 receptors in rat hippocampal slice models of ischemic tolerance

Abstract: Activation of glutamate receptors has been proposed as a key factor in the induction of ischemic tolerance. We used organotypic rat hippocampal slices exposed to 30 min oxygen-glucose deprivation (OGD) to evaluate postischemic pyramidal cell death in the CA1 subregion. In this model, 10 min exposure to OGD 24 h before the exposure to toxic OGD was not lethal and reduced the subsequent OGD neurotoxicity by 53% (ischemic preconditioning). Similarly, a 30 min exposure to the group I mGlu receptor agonist DHPG (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 33 publications
4
21
0
1
Order By: Relevance
“…On the contrary, Bao et al [2] used an adult rat model of focal brain ischemia and reported neuroprotection provided by the selective mGluR5 agonist CHPG. Meli et al [23] reported that CHPG failed to exacerbate neuronal damage in an in vitro model of rat organotypic hippocampal slices challenged with oxygen-glucose deprivation (OGD), while the activation of group I mGluRs by DHPG was shown to induce tolerance of OGD in the same model [31,40]. Consistent with these data, in our present study we observed only a nonsignificant trend toward an exacerbation of ischemia-evoked brain damage induced by ADX47273.…”
Section: Discussionsupporting
confidence: 82%
“…On the contrary, Bao et al [2] used an adult rat model of focal brain ischemia and reported neuroprotection provided by the selective mGluR5 agonist CHPG. Meli et al [23] reported that CHPG failed to exacerbate neuronal damage in an in vitro model of rat organotypic hippocampal slices challenged with oxygen-glucose deprivation (OGD), while the activation of group I mGluRs by DHPG was shown to induce tolerance of OGD in the same model [31,40]. Consistent with these data, in our present study we observed only a nonsignificant trend toward an exacerbation of ischemia-evoked brain damage induced by ADX47273.…”
Section: Discussionsupporting
confidence: 82%
“…When considering the influence of mGluR I specific ligands in models of neuronal apoptotic-like PCD, there are data showing that an agonist of this receptor, DHPG attenuates neuronal cell damage induced by some pro-apoptotic factors, such as staurosporine, etoposide or NMDA (Allen et al, 2000;Blaabjerg et al, 2003). However, a cautionary note here is the linkage of mGluR I to IP3-sensitive calcium pools which could under some conditions exaggerate the neuronal cell death (Nicoletti et al, 1999;Pshenichkin et al, 2008;Werner et al, 2007) as it has been shown for example for DHPG (20 μM) in a model of neuronal cell death induced by oxygen-glucose deprivation (Allen et al, 2000). Moreover, it has been shown that higher concentration of DHPG (5 mM) could induce cell death in striatal neurons, which is executed by apoptotic-and necrotic-like mechanisms (Diwakarla et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Pharmacological blockade of mGlu1 receptors enhances GABAergic transmission in the hippocampus by preventing the mGlu1-receptor mediated formation of endocannabinoids and the ensuing activation of inhibitory CB1 receptors localized on GABAergic nerve terminals (Landucci et al, 2009). In contrast, it is the activation of mGlu1 receptors that mediates the mechanism of ischemic tolerance observed with the paradigm of “ischemic preconditioning” in hippocampal slices (Werner et al, 2007), whereas activation of both mGlu1 and mGlu5 receptors mediates mechanisms of “ischemic post-conditioning” (Scartabelli et al, 2008). In cultured neurons challenged with excitotoxins mGlu1 receptor antagonists are consistently neuroprotective, whereas agonists can be neurotoxic or neuroprotective depending on the experimental paradigm (reviewed by Nicoletti et al, 1999).…”
Section: Detailed Description Of Mglu Receptor Subtypesmentioning
confidence: 99%